COST EFFECTIVENESS ANALYSIS NEUROPROTEKTIF CITICOLIN INJEKSI TUNGGAL DAN KOMBINASI PADA PASIEN STROKE ISKEMIK DI RUMAH SAKIT BHAKTI WIRA TAMTAMA SEMARANG - Ardianti, Djulia Shiendy Soes; Palupi, Dwi Hadi Setya; Sari, Wulan Kartika (Dian Nuswantoro Semarang, 2025)
Neuroprotective drugs are used to reduce the occurrence of cell damage due to obstruction of blood flow that supplies oxygen to the brain, thus limiting the tissue that experiences ischemia. However, the relatively high cost of treatment in ischemic stroke patients requires a cost-effectiveness analysis. The purpose of this study was to determine the characteristics of ischemic stroke patient treatment and the cost-effectiveness between the use of the neuroprotective drug citicoline and the combination of citicolin-piracetam injections at Bhakti Wira Tamtama Hospital Semarang. This study is a descriptive study with retrospective data collection techniques and purposive sampling. The effectiveness of neuroprotective drugs used in ischemic stroke patients was assessed from the average length of stay or LOS. The average LOS in the study was 3.17 days for a single citicolin injection and 3.7 days for a combination of citicolin-piracetam injections. Cost-Effectiveness Analysis was obtained by calculating the Average Cost Effectiveness Ratio (ACER) value of the average direct medical costs of using a single citicolin and a combination of citicolin-piracetam injections. Based on the ACER calculations, the most cost-effective neuroprotective drug is the combination of citicoline-piracetam injections with an ACER value of 1,651,786/day.